Exploration of Typeface Design within Wim Crouwel’s Modernist Aesthetic: A Formal and Experimental Inquiry into Typographic Form - Vera Vellina (Jurnal Desain Komunikasi Visual, 2025)
The objective of this study is to design and develop a typeface that embodies both formal clarity and experimental flexibility, drawing inspiration from Wim Crouwel’s modernist design philosophy while adapting it to the demands of contemporary digital applications. The research applies a design-based methodology that combines several stages: visual analysis of Crouwel’s typographic works, exploration of modular and grid-based principles, iterative sketching, digital prototyping, and evaluative feedback through critical review and testing of legibility. This systematic approach ensures that the design process not only honors Crouwel’s aesthetic but also responds to current practices in visual communication. The outcome of the study is a custom-designed experimental typeface constructed through modular principles, highlighting geometric precision and structural consistency while preserving usability across different media formats. The typeface demonstrates how grid-based construction can support legibility without limiting opportunities for experimentation in form. The findings suggest that reinterpreting Crouwel’s principles in a contemporary setting enriches typographic practice by bridging historical modernist aesthetics with innovative approaches to letterform design. The study concludes that modernist ideals, when critically adapted, remain relevant to current design challenges. They provide a framework for balancing clarity and experimentation, enabling typography to serve as both a functional medium of communication and an expressive tool for cultural and artistic exploration.